PERBANDINGAN PEER ATTACHMENT PESERTA DIDIK BERDASARKAN JENIS KELAMIN (Studi Komparatif terhadap Peserta Didik SMA Negeri 9 Bandung Tahun Ajaran 2019/2020) - Risa Agustin, - (2020)
This study analyzed the comparison of students' peer attachment based on gender. The purpose of this study is to find the difference of students' peer attachment based on gender generaly at each grade level. This study used quantitative research method with comparative descriptive. The samples of this study was 221 students of 10th, 11th and 12th grade of SMA Negeri 9 Bandung in 2019/2020 academic year used proportional stratified random sampling technique. To collect the data researcher used a peer attachment instrument that was developed from the original instrument of the peer attachment, namely parent inventory and revised peer-attachment (IPPA-R). To collect the gender data, researcher used the students' identities written in questionnaire. The comparative analysis was performed using non-parametric statistics. The technique was comparing between Two Independent Sample Test on peer attachment scores based on gender and K Independent Sample Test on peer attachment scores based on grade. The results showed that in general, the students' peer attachment of SMA Negeri 9 Bandung in 2019/2020 academic year were in the anxious-ambivalent attachment category. The results of hypothesis indicate that there are no differences between students' peer attachment scores either by gender or grade level. This research give a group guidance and group counseling service that can improve the quality of peer attachment. Keywords: peer attachment, gender, grade level, high school, comparative